Future Professions in Social Sciences - Gülen, Salih; Dönmez, Ismail ([EN], 2021)
It can be said that individuals' interests-abilities and social changes are effective in their choice of profession. In this study, professions that are likely to be popular in the future in the field of social sciences are examined. This study, based on national and international literature, is a compilation study. It can be said that the profession preferences of the individual have become clear due to important global changes such as pandemic, industry 4.0, immigration, 5G, space studies and education-related reasons that affect the society in the 21st century. Although it is likely that popular professions will turn to the fields of health and digitalization in the future, it is expected that occupational groups that can be evaluated within the social sciences in areas such as education, health, informatics, agriculture, arts, sports and music are also expected to be at the forefront.

Bireylerin ilgi-yeteneklerinin ve toplumsal degisimlerin meslek tercihlerinde etkili oldugu söylenebilir. Bu arastirmada sosyal bilimler alaninda gelecekte popüler olmasi muhtemel meslekler incelenmistir. Ulusal ve ulusal arasi literatüre dayanan bu çalisma bir derleme çalismasidir. 21. Yüzyilda toplumu etkileyen, pandemi, endüstri 4.0, göç, 5G, uzay çalismalari gibi önemli küresel degisimler ve egitimden kaynakli nedenlerden dolayi bireyin meslek tercihlerinin netlestigi söylenebilir. Gelecekte popüler mesleklerin saglik ve dijitallesme alanlarina yönelmesi muhtemel olsa da egitim, saglik, bilisim, tarim, sanat, spor ve müzik gibi alanlarda sosyal bilimler içerisinde degerlendirilebilecek meslek gruplarinin da ön planda olmasi beklenmektedir.
Sosyal Bilimlerde Gelecegin Meslekleri
Keywords: Sociology (Other); Sosyoloji (Diger)